Electronic and magnetic properties of Fe-doped narrow zigzag boron nitride nanoribbons. (March 2020) - Yin, Jie; Yang, Zhihong; Bi, Lan; Ren, Shanling; Yan, Gang; Wang, Yunhui; Huang, Xin
Graphical abstract: Abstract: The electronic structures and magnetic properties of single Fe-doped in the different substitutional sites for narrow zigzag boron nitride nanoribbons are studied based on density functional theory. By examining the total energy and formation energy, we predict that doping Fe in the substitutional 4B-site is more favorable than other sites in our calculated narrow zigzag boron nitride nanoribbons. The behavior of doping single Fe in the zigzag boron nitride nanoribbons drives the system to tend to show a spin polarized state, and the induced magnetic moment depends on the substitutional sites. The calculated electronic structures show that Fe-doped narrow zigzag boron nitride nanoribbon becomes a semiconductor with a direct energy gap, while the pristine boron nitride nanoribbon is an insulator with an indirect wide energy gap. The molecular dynamic simulation results predicate that single Fe-doped narrow zigzag boron nitride nanoribbons can exist stably under the realistic environment.